MODERN APPLICATION FOR IMPROVING AND REHABILITATING PRISONERS' MENTAL HEALTH - Yonata Laia; Jepri Banjarnahor; Oloan Sihombing; Haposan Lumbantoruan (LPPM Nusa Mandiri, 2025)
This study evaluates the Fuzzy Tsukamoto method as an effective rehabilitation solution for young inmates facing mental health challenges, including pre-existing conditions, confinement stress, and educational deficits. Mental health issues in correctional facilities remains a growing concern, affecting not only the well-being of inmates but also their chances of successful reintegration into society. The method employs Electroencephalogram/EEG to monitor tracked brain activity, providing real-time data that refined the treatment protocols and allowed for personalized adjustments. Conducted in a correctional facility in Medan, Indonesia, the study found significant reductions in anxiety and depression among participants, along with improved self-efficacy and emotional resilience. The results highlight the potential of the Fuzzy Tsukamoto method in not only improving inmate mental health but also in reducing recidivism rates and supporting social reintegration. These findings underscore the critical need to adopt more rehabilitative correctional strategies to address the complex mental health challenges within the incarcerated population.